New Means of Canine Leishmaniasis Transmission in North America: The Possibility of Transmission to Humans Still Unknown - Christine A. Petersen (Interdisciplinary Perspectives on Infectious Diseases)
At present it is not possible to determine in advance the outcome of Leishmania infantum infection. Canine Visceral Leishmaniasis (VL), caused by Le. infantum, is a natural disease process which offers a insight into the interaction of the host and resultant disease outcome. Canine VL results in the same altered pathophysiology and immunodysregulation seen in humans. VL in US dogs is likely to be transmitted primarily via nontraditional, nonvector means. VL mediated by Le. infantum is endemic in U.S. Foxhound dogs, with vertical transmission likely to be the novel primary means of transmission. This population of dogs offers an opportunity to identify host factors of natural disease. Prevention of human clinical visceral leishmaniasis can occur only by better understanding the disease ecology of the primary reservoir host: the dog.